Preparation and Characterization of Olmesartan Medoxomil-Loaded Polymeric Mixed Micelle Nanocarrier - Halah Talal Sulaiman; Nawal A. Rajab (Iraqi Journal of Pharmaceutical Sciences, 2025)
Olmesartan medoxomil (OLM) is a selective angiotensin II antagonist that effectively lowers blood pressure. It has a poor rate of absorption when taken orally, a maximum bioavailability of about 26%, and limited solubility in water. OLM is therefore categorized as class II in the Biopharmaceuticals Classification System (BCS), suggesting that it has high permeability and low solubility. By generating nanomicelles, this work attempts to increase the aqueous solubility and dissolution rate of OLM. Mixed polymeric nanomicelles made up of soluplus (SLP) with tween 80 (TWN80) and SLP with d-α tocopheryl polyethylene glycol 1000 succinate (TPGS), had been prepared in different gravimetric ratios. The nanomicelles holding OLM were developed using the film hydration technique and assessed for their particle size, polydispersity index (PDI), entrapment efficiency (EE%), and drug loading capacity (DL%), of the micellar dispersion. The optimized F4 formula comprising 100 mg SLP and 60 mg TWN 80 displayed a particle size of about 71.1±1.28 nm, PDI of 0.116±0.021, an EE% of 92±1.5, a DL% of 11.5±1.43, and enhanced in-vitro release compared to aqueous drug suspension. Using iodine as a hydrophobic probe, the critical micelle concentration (CMC) of F4 was determined to be 0.0112±0.001 mg/ml, which is lower than the theoretically computed CMC of 0.01284 mg/ml calculated using an equation. The preparation of F4 by the direct dissolution method was also established at different stirring periods (3,12, and 24 hours) and by two techniques, to evaluate the effect of the preparation method on particle size, PDI, EE%, and DL%. The results showed a significantly larger particle size, PDI, and lower EE% (p<0.05) than the thin film hydration method. Furthermore, the physical and chemical characteristics of F4 mixed nanomicelles were monitored over three months, both at room temperature and under refrigerated circumstances (4°C), and it was determined that the nanomicelles remained stable. The morphological analysis was conducted using a field emission scanning electron microscope (FESEM), which detected the presence of nanostructures with a spherical form and a diameter that matched the particle size measurements. The results of the existing study confirmed that OLM mixed nanomicelles are likely nanocarriers to improve solubility.